2011
DOI: 10.1109/tbme.2010.2095851
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Electrochemical Detection Method for Chlamydia trachomatis : Application for Point-of-Care Diagnostics

Abstract: Atlas Genetics has developed a Point-of-Care device for Chlamydia trachomatis utilizing a novel electrochemical detection principle. The assay has a time-to-result of less than 25 minutes. An independent pre-clinical validation study using 306 pre-typed clinical samples determined a clinical sensitivity of 98.1% and specificity of 98.0%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 5 publications
(4 reference statements)
0
23
0
1
Order By: Relevance
“…1516 Sadly, we have few good Federal Drug Administration-approved POC tests, 17 other than for HIV and trichomonas in the USA, 18 but several promising ones are in development. 1920 …”
Section: Diagnosis and Treatment Issuesmentioning
confidence: 99%
“…1516 Sadly, we have few good Federal Drug Administration-approved POC tests, 17 other than for HIV and trichomonas in the USA, 18 but several promising ones are in development. 1920 …”
Section: Diagnosis and Treatment Issuesmentioning
confidence: 99%
“…However, the GeneXpert platform fails to fulfil the ASSURED criteria (affordable, sensitive, specific, user-friendly, rapid, equipment-free, delivered to those who need it),13 stated by WHO, for rapid POC tests, for example, because the assays take around 90 min from sample to result, needs a source of electricity and is costly. Most recently, a rapid molecular POC test for C. trachomatis was approved in Europe (Atlas Genetics io),14 with a 30 min turnaround time, and many additional rapid molecular POC tests for non-viral STIs are in the pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Since the previous literature review [7], 4 studies have been published on the performance of investigational CT POC tests [64][65][66][67]. Hesse et al evaluated the performance of 4 novel CT POC prototypes in succession, each modified based on communication with the manufacturer, on vaginal and cervical swabs compared with SDA [64].…”
Section: Discussionmentioning
confidence: 99%
“…Dean et al evaluated the performance of a novel microfluidic multiplex PCR POC test on cervical swabs compared with the Roche Amplicor NAAT (PCR) and found that the sensitivity and specificity for the multiplex assay was 91.5% and 100% vs 62.4% and 95.9% for NAAT; discordant results between the multiplex assay and NAAT were evaluated using microfluidic Sanger sequencing [66]. Pearce et al evaluated the performance of a novel CT POC test using an electrochemical detection method on 306 samples previously pretyped as either CT positive (n = 107) or CT negative (n = 199) by TMA or PCR and found that the sensitivity and specificity for the novel POC test were 98.1% and 98.0%, respectively [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation